2005
DOI: 10.1097/01.brs.0000153703.80747.16
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Unilateral Fixation With Interbody Cages

Abstract: In the group of unilateral fixation combining PLIF with two cages, the anterior support of cages enabled unilateral instrumentation to restore torsional stiffness and other spinal stability indexes. Considering the initial stability and the load-sharing effect, this study showed that the unilateral fixation combining PLIF and two cages might be a good alternative to spinal fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 26 publications
3
50
0
1
Order By: Relevance
“…Unilateral pedicle screw fixation has been previously studied biomechanically and clinically. Some biomechanical studies using cadaver specimens have indicated that the unilateral instrumented TLIF procedure provides less rotational stability and stiffness than bilateral pedicle screw fixation, but whether the more rigid fixation is needed was controversial [8,23]. Encouraging results can be achieved by unilateral fixation with an anterior supporting device such as an interbody cage [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unilateral pedicle screw fixation has been previously studied biomechanically and clinically. Some biomechanical studies using cadaver specimens have indicated that the unilateral instrumented TLIF procedure provides less rotational stability and stiffness than bilateral pedicle screw fixation, but whether the more rigid fixation is needed was controversial [8,23]. Encouraging results can be achieved by unilateral fixation with an anterior supporting device such as an interbody cage [23].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]. Some clinical and biomechanical studies on the suitability of unilateral pedicle screw fixation have demonstrated that reliable fusion with fewer pedicle screws can be achieved [11][12][13][20][21][22][23]. Therefore, the need for unilateral or bilateral instrumentation is a matter for debate.…”
Section: Discussionmentioning
confidence: 99%
“…U nilateral pedicle screw fixation has been found to achieve stability and fusion rates similar to those of bilateral pedicle screw fixation in the treatment of patients with single-segment degenerative lumbar instability, 1,3,7,12,18 as well as in the treatment of patients with double-segment degenerative lumbar instability. 3,18 However, these studies used conventional lumbar fusion surgery that has drawbacks, such as the need for extensive soft tissue dissection with resulting iatrogenic tissue injury, which can lead to increased pain postoperatively, longer recovery duration, and impairment of spinal function.…”
mentioning
confidence: 99%
“…It is true that the hemilaminectomy approach may provide a relatively narrow exposure of the spinal canal, but does more decompression lead to a better clinical result? The surgical results for multilevel continuous/mixed cervical ossification of posterior longitudinal ligament involves various aspects, including neurological function and complications (especially C5 palsy and kyphosis) at short-and long-term followup.Previous studies [1,3] reported that unilateral fixation had comparable efficacy to bilateral fixation in lumbar spinal fusion. Unilateral fixation is one of the remarkable novel ideas of this technique.…”
mentioning
confidence: 97%
“…Previous studies [1,3] reported that unilateral fixation had comparable efficacy to bilateral fixation in lumbar spinal fusion. Unilateral fixation is one of the remarkable novel ideas of this technique.…”
mentioning
confidence: 97%